If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -9 = 39 + -2x Reorder the terms: -9 + 6x = 39 + -2x Solving -9 + 6x = 39 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -9 + 6x + 2x = 39 + -2x + 2x Combine like terms: 6x + 2x = 8x -9 + 8x = 39 + -2x + 2x Combine like terms: -2x + 2x = 0 -9 + 8x = 39 + 0 -9 + 8x = 39 Add '9' to each side of the equation. -9 + 9 + 8x = 39 + 9 Combine like terms: -9 + 9 = 0 0 + 8x = 39 + 9 8x = 39 + 9 Combine like terms: 39 + 9 = 48 8x = 48 Divide each side by '8'. x = 6 Simplifying x = 6
| -18b+1=17-16b | | -20-20+10p=20+13p | | 3x+8=2x+35 | | (-4)+3=14 | | Y+72=4(6+Y) | | 195-8y+y^2=180 | | 10c+8=9c | | 10-8r=-8-5r | | -9m-10=-1-7m+1 | | -5(-1x+8)=-45 | | x*.13=102 | | -7-3d=-2d | | (2n+19)+(4n+17)=180 | | 8+5n=7n-8 | | -8k=-10k+10 | | (2x+9)= | | (6x^2)-(5x)-6=0 | | 3-2h=-7-7h | | x+y^2=180 | | 3(7x+8)=-81 | | 8(6n-1)-7=-111 | | 3+5n+2(n-2)=62 | | 3u=4+4u | | (2n+16)+(3n+34)=180 | | 10+6v=7v | | 7(4-6x)=322 | | 3t=-t-8 | | -8+z=2z | | (2(-1)-6)= | | R+8r=16 | | 6(p+.04)=5(p-1.2) | | 12(.33)= |